Situación de la Dirofilaria immitis en caninos atendidos en la clínica veterinaria Terranova en la ciudad de Popayán - Cauca (2020)
The canine dirophilariosis or "heartworm", it is a zoonotic disease transmitted by vectors of the genus Culex, Aedes and Anophelex, which host the larval phase of the parasite nematode Dirofilaria immitis, it applies to mammals, including dogs and humans, it generates pathologies as the dirophilariosis cardiopulmonary, the dirophilariosis subcutaneous and ocular in dogs, unleashing many signs and symptoms that could end the patient's life. Thus, this project was oriented to search for adult canines that presented the parasite and that through the kit of quick test Ag heartworm canine 2.0 confirmed by the Terranova veterinary addressed in Popayán city, with the purpose of contribute knowledge to the veterinary doctors and the students about the relevance of this test in the clinic as differential diagnostic.